Predictors of inadequate bowel preparation using two liters of polyethylene glycol for colonoscopy - Parajuli, Anuj; KC, Niranjan (Journal of Kathmandu Medical College, 2020)
Background: Inadequate bowel preparation can result in missed pathological lesions and cancellation of procedures thereby increasing the cost and delay in the diagnosis. Objectives: Thes aim of the study was to identify the potential predictors of inadequate bowel preparation using 2 liters of polyethylene glycol solution. Methodology: A prospective study was done, which included 138 consecutive patients who underwent colonoscopy over a period of 6 months. Patient’s demographics, medical history, and preparation quality were collected and compared. Factors associated with inadequate bowel preparation were identified by univariate statistics and multivariate logistical regression analysis. Results: Out of 138 colonoscopy procedure, 119 (86.2%) preparations were adequate and 19 (13.8%) were inadequate. The mean age of the patient was 52.62 (SD ±10.51) years. Out of which, 82 (59.4%) were male and 56 (40.6%) were female. In the multivariate regression analysis, constipation [adjusted OR 8.55, 95% CI 1.79-41.67] and non-compliance [adjusted OR 58.82, 95% CI 5.99-500] were independently associated with inadequate bowel preparation. Conclusion: Constipation, non-compliance, overweight, neurological disorders like stroke, dementia and age >60 years were associated with inadequate bowel preparation. Early identification of patients with a high risk of inadequate preparation can be salvaged with change in bowel cleaning strategy.